Coronary artery spasm: a Quandary - Ngow, Harris Abdullah; Wan Mohd Nowalid, Wan Khairina (2011)
Coronary artery spasm can result in acute coronary syndrome. This vasospastic syndrome can cause profound morbidity and mortality as a significant proportion of patients continue to have angina despite optimal medical therapy. We illustrate the dilemma in managing a young woman who presented with non ST-segment myocardial infarction as a result of it. She did not have the conventional risks for coronary artery disease except the family history of myocardial infarction. Vasospasm was demonstrated at the mid right coronary artery which resolved with intracoronary nitroglycerine during angiogram. Most women with no significant heart disease following demonstration of normal or “near normal” coronary arteries after angiography are offered no treatment beyond reassurance each year. New data suggest that this approach may no longer be appropriate and the prognosis in such patient is not as benign as previously thought. We discuss the management dilemma of such patient with associated mild atherosclerotic plaque.